Urbanization and Economic Development in Indonesia: Demographic Perspectives Analysis - Mustafa Elnagi Elsamani Hassan; Agus Joko Pitoyo (Populasi, 2017)
The level of urbanization has increased from 17.2% to 49.7% in the last three decades. The urbanization process in Java is occurring more dramatically and rapidly compared to that in outer Java. There is a growing trend of urbanization in the Java Islands, where the level of urbanization has increased from 11.55% to 33.64% in 1971-2010. The ratio of urban population of all the provinces in Indonesia was greater than 20% in 2010 exclude East Nusa Tenggara. There is a strong positive relationship between the level of regional economic development and level of urbanization. Evaluation of urbanization can be improved from two aspects: first, the forward conditions of urbanization can be analyzed, such as the number of non-farm jobs, infrastructure level and the supply capacity of public services. Second, the forward effects of urbanization should be comprehensively evaluated, including economic, social, and environmental sustainability.